Maintaining (Locus of) Control? Assessing the Impact of Locus of Control on Education Decisions and Wages - Rémi Piatek; Pia Pinger (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper establishes that individuals with an internal locus of control, i.e., who believe that reinforcement in life comes from their own actions instead of being determined by luck or destiny, earn higher wages. However, this positive effect only translates into labor income via the channel of education. Factor structure models are implemented on an augmented data set coming from two different samples. By so doing, we are able to correct for potential biases that arise due to reverse causality and spurious correlation, and to investigate the impact of premarket locus of control on later outcomes.
Keywords: C31; J24; J31; 330; locus of control; wages; latent factor model; data set combination; Persönlichkeitspsychologie; Bildungsverhalten; Bildungsertrag; Lohn; Schätzung; Deutschland